Firm Size as a Moderator of the Effects of Financial Leverage and the Investment Opportunity Set on Financial Performance - Purwanti Purwanti; Endah Salsabila Anggraeni; Petty Aprilia Sari; Suhariyanto (STIE Amkop Makassar, 2026)
This study examines the effects of financial leverage, proxied by the debt-to-equity ratio (DER), and the investment opportunity set (IOS), proxied by the market-to-book value of equity (MBVE), on financial performance measured by economic value added (EVA). It also evaluates the moderating role of firm size. The sample comprises 51 property and real estate companies listed on the Indonesia Stock Exchange during 2020-2024 and selected through purposive sampling. Panel data were analyzed in EViews 12 using a fixed-effects model and moderated regression analysis. DER has a significant negative effect on EVA, whereas IOS has no significant effect. Firm size significantly moderates the DER-EVA relationship: the negative interaction coefficient indicates that size intensifies the adverse association between leverage and EVA. Conversely, firm size does not moderate the IOS-EVA relationship. These findings suggest that the funding advantages of large firms may be offset by higher debt-related costs, agency costs, and organizational complexity. Large property firms should therefore exercise tighter control over leverage and ensure that debt-funded investments generate returns above the cost of capital. The study integrates leverage, growth opportunities, firm size, and EVA within a panel-data framework for an emerging-market property sector.